2020
DOI: 10.1186/s40478-020-01002-8
|View full text |Cite
|
Sign up to set email alerts
|

The carboxyl termini of RAN translated GGGGCC nucleotide repeat expansions modulate toxicity in models of ALS/FTD

Abstract: An intronic hexanucleotide repeat expansion in C9ORF72 causes familial and sporadic amyotrophic lateral sclerosis (ALS) and frontotemporal dementia (FTD). This repeat is thought to elicit toxicity through RNA mediated protein sequestration and repeat-associated non-AUG (RAN) translation of dipeptide repeat proteins (DPRs). We generated a series of transgenic Drosophila models expressing GGGGCC (G 4 C 2) repeats either inside of an artificial intron within a GFP reporter or within the 5′ untranslated region (UT… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 15 publications
(16 citation statements)
references
References 73 publications
0
16
0
Order By: Relevance
“…Expression of siRNAs against SF2/SRSF1 was able to significantly reduce necrosis and prohibit shrinkage of GGGGCC repeat expressing fly eyes ( Figure 3D-E). Next, we tested if SR proteins modulate GGGGCC repeat elicited shortening of lifespan (He et al, 2020). As with CGG repeats, ubiquitous expression of siRNA against SRSF1 significantly enhanced survival of GGGGCC repeat expressing fly ( Figure 3F).…”
Section: Sr Proteins Modify Ggggcc Repeat Rna Toxicity In Drosophilamentioning
confidence: 98%
See 1 more Smart Citation
“…Expression of siRNAs against SF2/SRSF1 was able to significantly reduce necrosis and prohibit shrinkage of GGGGCC repeat expressing fly eyes ( Figure 3D-E). Next, we tested if SR proteins modulate GGGGCC repeat elicited shortening of lifespan (He et al, 2020). As with CGG repeats, ubiquitous expression of siRNA against SRSF1 significantly enhanced survival of GGGGCC repeat expressing fly ( Figure 3F).…”
Section: Sr Proteins Modify Ggggcc Repeat Rna Toxicity In Drosophilamentioning
confidence: 98%
“…Thus, we asked if SR proteins that interact with CGG repeats and rescued CGG repeat toxicity in our fly screen may modulate GGGGCC repeat toxicity in a Drosophila model. To this end, we used a transgenic Drosophila model expressing UAS-driven 28 GGGGCC repeats that exhibits a rough-eye phenotype when expressed in fly eyes (He et al, 2020). We found that Drosophila homologs of several SR proteins, including SF2/SRSF1, SRSF2/8 and 4/6, significantly reduced rough-eye phenotypes in the GGGGCC repeat expressing fly ( Figure 3A-B).…”
Section: Sr Proteins Modify Ggggcc Repeat Rna Toxicity In Drosophilamentioning
confidence: 99%
“…This can be explained by the finding that in the antisense strand, poly-GP is translated via AUG-initiated translation as well as RAN translation, whereas in the sense strand poly-GP is translated through RAN translation ( Zu et al, 2013 ; Tabet et al, 2018 ). Intriguingly, the C-terminal region of RAN-translated proteins can influence their cellular distribution and relative toxicity ( He et al, 2020 ), suggesting that poly-GP produced from either the sense or the antisense strand could have different biochemical properties and interacting partners.…”
Section: Insights Into Ran Translation and Production Of Dprsmentioning
confidence: 99%
“…Identification of new DPR species implies that the composition of DPRs appears to be much more complicated than previously speculated. As the immediate sequence surrounding the repeat region can alter the behavior, localization, and toxicity of DPRs ( He et al, 2020 ), future work should also consider both C and N-terminus amino acids to more accurately portray the role of each DPR in C9ORF72 ALS/FTD pathogenesis. Thus, to better understand how DPRs contribute to disease, future research should focus on disease models that express multiple DPRs, ideally at physiologically relevant levels.…”
Section: Future Directions and Conclusionmentioning
confidence: 99%
“…To assess the role of these factors in an in vivo model of repeat toxicity, we used transgenic Drosophila lines conditionally expressing 28 GGGGCC repeats under the UAS promoter, with the repeat inserted into either the second chromosome or third chromosome (35). When expressed with a non-targeting control shRNA in the fly eye using the eye-specific GMR-Gal4 driver, the repeat causes a severe rough eye phenotype with noticeable eye shrinkage (Figure 5A & B) (35).…”
Section: Denr Kd Prolongs Lifespan Of Drosophila Expressing Ggggcc Repeatmentioning
confidence: 99%